2023
DOI: 10.1007/s00359-023-01642-w
|View full text |Cite
|
Sign up to set email alerts
|

“It is becoming increasingly difficult to find reviewers”—myths and facts about peer review

Abstract: A frequent complaint of editors of scientific journals is that it has become increasingly difficult to find reviewers for evaluating submitted manuscripts. Such claims are, most commonly, based on anecdotal evidence. To gain more insight grounded on empirical evidence, editorial data of manuscripts submitted for publication to the Journal of Comparative Physiology A between 2014 and 2021 were analyzed. No evidence was found that more invitations were necessary over time to get manuscripts reviewed; that the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“… 26 30 Table 1 provides a succinct summary of some proposed innovations in current literature. This includes for instance a more efficient involvement of editors in the selection of prospective reviewers, 31 improving diversity, 32 training reviewers and opening up the peer review process. 7 Others have argued that peer reviewers are rejecting invitations not necessarily because of lack of time but presumably because of lack of motivation.…”
Section: No More Motivation To Review For Freementioning
confidence: 99%
“… 26 30 Table 1 provides a succinct summary of some proposed innovations in current literature. This includes for instance a more efficient involvement of editors in the selection of prospective reviewers, 31 improving diversity, 32 training reviewers and opening up the peer review process. 7 Others have argued that peer reviewers are rejecting invitations not necessarily because of lack of time but presumably because of lack of motivation.…”
Section: No More Motivation To Review For Freementioning
confidence: 99%
“…As an editorial team we are systematically removing those reviewers in our database who repeatedly do not respond to requests for review in order to speed up the review process for authors. A study of reviews for the Journal of Comparative Physiology found that another factor contributing to the amount of time an article spends in the review process is the increasing number of late reviews (Zupanc, 2023). Between 2014 and 2021 they found that the average number of days for late reviewers to submit their reviews almost doubled.…”
Section: Challenges To Peer Reviewmentioning
confidence: 99%
“…Secondly, if the potential of GenAI to enhance productivity does get realized, the question arises of how authors, journal editors and reviewers will deal with the consequent growth in article submissions and in the volume of published literature. Whether or not finding reviewers for papers submitted to academic journals has generally become more challenging is currently a disputed issue (compare for instance Flaherty, 2022, with Zupanc, 2023), yet there is little doubt that GenAI could make such a challenge very real. Unless the efficiency of the reviewing process can somehow be enhanced in proportion to the rise in submitted articles, journals are likely to face a growing backlog of submissions.…”
mentioning
confidence: 99%